KEPEMIMPINAN TRANSFORMASIONAL BERBASIS NILAI ISLAM: STRATEGI PENINGKATAN KUALITAS PEMBELAJARAN DI SEKOLAH SMA MIFTAHUL ULUM - Arifin, Syamsul; Wahab, Wahab; Prabowo, Sugeng Listyo (Universitas Tanjungpura, 2026)
This study examines the application of transformational leadership by the principal of SMA Miftahul Ulum, an Islamic secondary school located in the rural area of Kubu Raya Regency, West Kalimantan, in an effort to enhance the quality of learning amidst limited resources. Using a qualitative case study approach, the research relied on interviews, observations, and document analysis. The findings reveal that the principal successfully implemented the four dimensions of transformational leadership idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration adapted through an Islamic perspective and local strategies. These strategies included optimizing the school